A comparative study of the elastic properties of Chinese NiTi to four different nickel titanium wires used as an initial archwire - Kua, Gay Suan.
The purpose of this research was to compare the elastic properties of Chinese NiTi with those of other Nickel Titanium alloys. 2 trials were conducted in order to eliminate biases in the accuracy of measurement. A preliminary trial of Chinese NiTi, NiTi Ormco, Nitinol SE, Reflex NiTi, and Elastinol each with 6 replicates was done in a thermoheat regulator of 37(degree centigrade) + 2 using millimeter graph scale paper for its measurement. The analysis of variance of repeated measures design was utilized to compare the springback characteristic of each wire and the effect of time on the amount of deformation. Results shows the subset 1 (Chinese NiTi, Reflex, and Elastinol) and subset 2 (Ormco NiTi, and Nitnol SE) reveal no significant differences from among themselves but a relevant difference between subset 1 and subset 2. Since the wires in subset 1 behave similarly, this group was again tested in a 2nd trial with 10 replicates of each wire sample. This time the samples were stored in a humidifier box of 25(degree centigrade) + 5 room temperature. Measurement was done using a millimeter reticle microscope in order to obtain a more accurate reading. Statistical results in the 2nd trial reveal no significant difference from among the 3 wires. A comparison of the microstructure was also taken using metallography techniques. The purpose of which is to see if there is difference in the microstructure of an unstrained and strained condition, and correlate findings with that of the result in the preliminary and the secondary trials. The microstructures of all the samples were single phase and contained stringers which could be Titanium Hydrogen compound (TiH) as obtained from literature. Results show that both strained and unstrained wire have similar microstructures without evidence of strain-induced martensitic transformation (SIMT).
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontic appliances; Orthodontics, Corrective; Nickel titanium alloys